UNIVERSAL MEASURING DEVICE UMD8-204 (Modern information system and technologies, 2018)
The article provides an analysis and a brief description of the created project, designed to simplify and reduce the use of computing and measuring devices in training and repair designing practice. Developed laboratory devices: signal generator, frequency meter and laboratory power supply. Questions are devoted to viewing and expanding their functionality, at the same time, with a decrease in cost.